Least-cost control strategy optimization for air quality attainment of Beijing–Tianjin–Hebei region in China. (1st September 2019) - Xing, Jia; Zhang, Fenfen; Zhou, Yang; Wang, Shuxiao; Ding, Dian; Jang, Carey; Zhu, Yun; Hao, Jiming
Abstract: Control strategies can be optimized to attain air quality standards at minimal cost through selecting optimal combinations of controls on various pollutants and regional sources. In this study, we developed a module for least-cost control strategy optimization based on a real-time prediction system of the responses of pollution concentrations to emissions changes and marginal cost curves of pollutant controls. Different from other method, in this study the relationship between pollution concentrations to and precursor emissions was derived from multiple air quality simulations in which the nonlinear interactions among different precursor emissions can be well addressed. Hypothetical control pathways were designed to attain certain air quality goals for particulate matter (PM2.5 ) and ozone (O3 ) in the Beijing–Tianjin–Hebei region under the 2014 baseline emission level. Results suggest that reducing local primary PM emissions was the most cost-efficient method to attain the ambient PM2.5 standard, whereas for O3 attainment, reducing regional emission sources of gaseous pollutants (i.e., SO2, NOx, and volatile organic compounds (VOCs)) exhibited greater effectiveness. NH3 controls may be cost-efficient in achieving strengthened PM2.5 targets; however, they might not help in reducing O3 . To achieve both PM2.5 (<35 μg m −3 ) and O3 (daily 1-h maxima concentration < 100 ppb) targets in Beijing, the reduced rates in BTH regions of NOx, SO2, NH3, VOCs and primary PM are 75%, 75%, 5%, 55%, and 85%, respectively from the emission levels in the year of 2014. Local reduction is the most effective method of attaining moderate PM2.5 and O3 targets; however, to achieve more aggressive air quality goals, the same level of reductions must be conducted across the whole Beijing–Tianjin–Hebei region. Highlights: A module of least-cost control strategy optimization was developed for air quality attainment. Local primary PM control was the most cost-efficient method of reducing PM2.5 NH3 controls may be cost-efficient in achieving strengthened PM2.5 target. Regional controls exhibit greater effectiveness for O3 attainment. Same level of reductions in local and regional sources are recommended to achieve more aggressive air quality goals.